The Dendritic Cell Response to Classic, Emerging, and Homeostatic Danger Signals. Implications for Autoimmunity - Gallo, Paul M.; Gallucci, Stefania (Frontiers in Immunology, 2013)
Dendritic cells (DCs) initiate and control immune responses, participate in the maintenance of immunological tolerance and are pivotal players in the pathogenesis of autoimmunity. In patients with autoimmune disease and in experimental animal models of autoimmunity, DCs show abnormalities in both numbers and activation state, expressing immunogenic levels of costimulatory molecules and pro-inflammatory cytokines. Exogenous and endogenous danger signals activate DCs to stimulate the immune response. Classic endogenous danger signals are released, activated, or secreted by host cells and tissues experiencing stress, damage, and non-physiologic cell death; and are therefore referred to as damage-associated molecular patterns (DAMPs). Some DAMPs are released from cells, where they are normally sequestered, during necrosis (e.g. heat shock proteins, uric acid, ATP, HMGB1, mitochondria-derived molecules). Others are actively secreted, like Type I Interferons. Here we discuss important DAMPs in the context of autoimmunity. For some, there is a clear pathogenic link (e.g. nucleic acids and lupus). For others, there is less evidence. Additionally, we explore emerging danger signals. These include inorganic materials and man-made technologies (e.g. nanomaterials) developed as novel therapeutic approaches. Some nanomaterials can activate DCs and may trigger unintended inflammatory responses. Finally, we will review “homeostatic danger signals”, danger signals that do not derive directly from pathogens or dying cells but are associated with perturbations of tissue/cell homeostasis and may signal pathological stress. These signals, like acidosis, hypoxia and changes in osmolarity, also play a role in inflammation and autoimmunity.